2014
DOI: 10.1016/j.rbmo.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Low-dosage clomiphene reduces premature ovulation rates and increases transfer rates in natural-cycle IVF

Abstract: Natural-cycle IVF has been suggested as an alternative IVF treatment. However, efficacy is limited due to high premature ovulation rates, resulting in low transfer rates. This study investigates whether low dosages of clomiphene citrate reduce premature ovulation rate and increase transfer rate. Of 112 women included (aged 35.2 ± 4.5 years) 108 underwent one natural-cycle IVF cycle with human chorionic gonadotrophin (HCG) to induce ovulation and 103 underwent one natural-cycle IVF cycle with 25 mg/day clomiphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…Thus, exogenous stimulation with gonadotropins, as widely practiced in current procedures of in vitro fertilisation for the induction of a multifollicular reaction, has many effects on the follicular mechanism and growth, not only triggering multiple follicle growth but also possibly negatively affecting follicular and oocyte function. Studies with naturally matured follicles have indeed shown that the implantation potential of oocytes obtained from natural cycle IVF (NC-IVF) follicles is higher than of those from conventionally gonadotropin stimulated (c-IVF) follicles (Aanesen et al, 2010;Gordon et al, 2013;Von Wolff et al, 2014b). Furthermore, a recent study from our laboratory has revealed that the follicular endocrinological milieu was significantly altered by conventional IVF stimulation protocols (Von Wolff et al, 2014a), suggesting that the exogenous stimulation affects follicular function.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exogenous stimulation with gonadotropins, as widely practiced in current procedures of in vitro fertilisation for the induction of a multifollicular reaction, has many effects on the follicular mechanism and growth, not only triggering multiple follicle growth but also possibly negatively affecting follicular and oocyte function. Studies with naturally matured follicles have indeed shown that the implantation potential of oocytes obtained from natural cycle IVF (NC-IVF) follicles is higher than of those from conventionally gonadotropin stimulated (c-IVF) follicles (Aanesen et al, 2010;Gordon et al, 2013;Von Wolff et al, 2014b). Furthermore, a recent study from our laboratory has revealed that the follicular endocrinological milieu was significantly altered by conventional IVF stimulation protocols (Von Wolff et al, 2014a), suggesting that the exogenous stimulation affects follicular function.…”
Section: Introductionmentioning
confidence: 99%
“…Further exclusion criteria for the study participation were current psychological treatment, serious psychiatric illness and insufficient knowledge of German. The women were counseled in accordance with our study results described elsewhere . These studies revealed that treatment time to achieve a pregnancy is 30% longer in NC‐IVF, whereas costs per achieved pregnancy are 30% lower.…”
Section: Methodsmentioning
confidence: 89%
“…The influence of these factors on the mental state of the couple and thus their psychological stress has largely been unstudied in detail up to now. Advances in IVF treatments without gonadotropin stimulation, NC‐IVF now represents an alternative form of treatment where pregnancy takes longer to occur but the success rate is good overall . Furthermore, the costs per pregnancy are lower , with injections, anesthesia for oocyte collection and embryo selection not being required .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations